2019
DOI: 10.1007/978-3-030-26203-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Computer and Information Literacy

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. Regarding these commercial rights a non-exclusive license has been granted to the publisher. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 16 publications
6
46
1
5
Order By: Relevance
“…Results of past studies on the difference in ICT integration into teaching between male and female teachers were also inconsistent across countries (Gebhardt et al 2019) and past studies (e.g., Aramide et al 2015;Oosterwegel et al 2004). Some studies reported significant sex effects on ICT use in education across different teacher samples and cohorts (Gebhardt et al 2019;Oosterwegel et al 2004;Sink et al 2009;Tondeur et al 2008;Volman and van Eck 2001).…”
Section: Demographic Variables and Ict Integration In Teachingmentioning
confidence: 94%
See 1 more Smart Citation
“…Results of past studies on the difference in ICT integration into teaching between male and female teachers were also inconsistent across countries (Gebhardt et al 2019) and past studies (e.g., Aramide et al 2015;Oosterwegel et al 2004). Some studies reported significant sex effects on ICT use in education across different teacher samples and cohorts (Gebhardt et al 2019;Oosterwegel et al 2004;Sink et al 2009;Tondeur et al 2008;Volman and van Eck 2001).…”
Section: Demographic Variables and Ict Integration In Teachingmentioning
confidence: 94%
“…Some studies reported significant sex effects on ICT use in education across different teacher samples and cohorts (Gebhardt et al 2019;Oosterwegel et al 2004;Sink et al 2009;Tondeur et al 2008;Volman and van Eck 2001). For instance, Gebhardt et al (2019) analyzed the sex differences in ICT use across 12 countries using the International Computer and Information Literacy Study (ICILS) 2013 of the International Association for the Evaluation of Educational Achievement (IEA). Differences were significant in eight of the 12 countries.…”
Section: Demographic Variables and Ict Integration In Teachingmentioning
confidence: 99%
“…Additionally, Eickelmann and Vennemann ( 2017 ) revealed that relatively younger teachers, mostly classified as ICT enthusiasts, reported a higher frequency of ICT usage in classes. Previous research showed that teachers’ age (Drossel et al, 2017a ; Drossel et al, 2017b ; Eickelmann & Vennemann, 2017 ; Siddiq et al, 2016 ), and gender (Drossel et al, 2017a ; Drossel et al, 2017b ) are influential on their ICT usage for teaching while Gebhardt et al ( 2019 ) found out no significant influence of gender.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Self-efficacy also functions as a mediator between learners’ ICT use and CIL (Hatlevik et al, 2018 ; Rohatgi et al, 2016 ). Lastly, Gebhardt et al ( 2019 ) demonstrated that learners’ interest in and enjoyment of ICT positively linked with their CIL.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation